2021
DOI: 10.1016/j.mayocp.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Severe COVID-19 Has Similarities to Sepsis-Associated Kidney Injury

Abstract: Objective To compare COVID-19 acute kidney injury (AKI) to sepsis-AKI (S-AKI) the morphology, transcriptomic and proteomic characteristics of autopsy kidneys were analyzed. Patients and methods Individuals 18 years and older who died from COVID-19 and had an autopsy performed at Mayo Clinic between April 2020 to October 2020 were included. Morphological evaluation of the kidneys of 17 individuals with COVID-19 was performed. In a subset of 7 COVID-19 cases with post-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…More recent data suggest that, though not entirely overlapping, ATI in COVID-19 may share similar molecular mechanisms as septic AKI. A recent multi-omics study of seven COVID-19 kidney autopsy specimens demonstrated a similar transcriptomic and proteomic profile to that of seven control samples with non-COVID-19 septic AKI, with both profiles prominently featuring the presence of mitochondrial dysfunction [62].…”
Section: Clinical and Histopathological Features Of Kidney Injury In ...mentioning
confidence: 83%
See 1 more Smart Citation
“…More recent data suggest that, though not entirely overlapping, ATI in COVID-19 may share similar molecular mechanisms as septic AKI. A recent multi-omics study of seven COVID-19 kidney autopsy specimens demonstrated a similar transcriptomic and proteomic profile to that of seven control samples with non-COVID-19 septic AKI, with both profiles prominently featuring the presence of mitochondrial dysfunction [62].…”
Section: Clinical and Histopathological Features Of Kidney Injury In ...mentioning
confidence: 83%
“…3.1. Tubular Injury and Tubular Dysfunction as Primary Features of COVID-19-Associated AKI Multiple case series, including autopsy and biopsy studies, have shown that kidney disease in the setting of COVID-19 is most commonly due to acute tubular injury (ATI), often somewhat less severe than would be expected for the clinical severity of AKI; however, multiple glomerular pathologies, especially collapsing glomerulopathy, have also been reported [17,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Collapsing glomerulopathy appears to occur most commonly in patients expressing high-risk APOL1 alleles [65][66][67][68][69][70][71].…”
Section: Clinical and Histopathological Features Of Kidney Injury In ...mentioning
confidence: 99%
“…In kidney transplant recipients, mortality rate ranged between 24%−32% 14 . Acute tubular injury is one of the most common pathology in SARS‐CoV2 infection 15,16 . In kidney transplantation, acute rejection is found in 9.2% of the kidney transplant tranrecipients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Mariam P. Alexander et al. ( 128 ) compared COVID-19 AKI with SA-AKI, and analyzed the morphological, transcriptome, and proteomic characteristics of postmortem kidneys. Transcriptomics found that COVID-19 AKI and SA-AKI have a rich transcriptional pathway associated with inflammation (apoptosis, autophagy, major histocompatibility complex I and II, and Type 1 T-assisted cell differentiation) compared to non-infectious AKI; Proteomic pathway analysis showed that both of them were enriched to a lesser extent in necrotic apoptosis and Sirtuin signaling pathways, both of which are involved in the regulatory response of inflammation.…”
Section: Multi-omics Integrationmentioning
confidence: 99%